High Hydrostatic Pressure-Based Combination Strategies for Microbial Inactivation of Food Products: The Cases of Emerging Combination Patterns - Xia, Qiang; Liu, Qianqian; Denoya, Gabriela I.; Yang, Caijiao; Barba, Francisco J.; Yu, Huaning; Chen, Xiaojia (Frontiers in Nutrition, 2022)
The high demand for fresh-like characteristics of vegetables and fruits (V&F) boosts the industrial implementation of high hydrostatic pressure (HHP) used for simultaneously maintaining organoleptic characteristics and achieving stabilization effect of the food, but there remains a great challenge for assuring complete microbial inactivation only relying on individual HHP treatments, including pressure-resistant strains and regrowth of injured microbes during the storage process. Traditional HHP-assisted thermal processing may compromise the nutrition and functionalities due to accelerated chemical kinetics under high-pressure conditions. This work summarizes the recent advances in emerging HHP-based combination strategies for microbial safety, of which the necessity is demonstrated by comparing the processing features with individual HHP and HHP-assisted thermal processing. Considerations and requirements about future process design and development of HHP-based combination technologies are also given.